2018
DOI: 10.1002/nbm.3912
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized ketone body metabolism in the rat heart

Abstract: The aim of this work was to investigate the use of 13C‐labelled acetoacetate and β‐hydroxybutyrate as novel hyperpolarized substrates in the study of cardiac metabolism. [1‐13C]Acetoacetate was synthesized by catalysed hydrolysis, and both it and [1‐13C]β‐hydroxybutyrate were hyperpolarized by dissolution dynamic nuclear polarization (DNP). Their metabolism was studied in isolated, perfused rat hearts. Hyperpolarized [1‐13C]acetoacetate metabolism was also studied in the in vivo rat heart in the fed and fasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
(101 reference statements)
4
33
0
Order By: Relevance
“…HP 13 C-AcAc was first reported as an imaging probe by Jensen et al 43 In that study, ethyl [1,[3][4][5][6][7][8][9][10][11][12][13] 44 This study demonstrated that metabolism of HP 13 C-ketones can be detected in the heart, and several downstream metabolites of the HP 13 C-agents were observed. We first reported with preliminary results that it is possible to correlate altered mitochondrial redox in perfused rat hearts with the production of HP-β-HB from HP-AcAc.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…HP 13 C-AcAc was first reported as an imaging probe by Jensen et al 43 In that study, ethyl [1,[3][4][5][6][7][8][9][10][11][12][13] 44 This study demonstrated that metabolism of HP 13 C-ketones can be detected in the heart, and several downstream metabolites of the HP 13 C-agents were observed. We first reported with preliminary results that it is possible to correlate altered mitochondrial redox in perfused rat hearts with the production of HP-β-HB from HP-AcAc.…”
Section: Discussionmentioning
confidence: 87%
“…HP 13 C‐AcAc was first reported as an imaging probe by Jensen et al In that study, ethyl [1,3‐ 13 C]AcAc was used as a marker for decreased esterase activity in liver tumors but HP‐β‐HB was not detected. Recently, Miller et al investigated the metabolism of HP‐[1‐ 13 C]AcAc and HP[1‐ 13 C]β‐HB in isolated, perfused rat hearts as well as in vivo . This study demonstrated that metabolism of HP 13 C‐ketones can be detected in the heart, and several downstream metabolites of the HP 13 C‐agents were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Using [3‐ 13 C]acetoacetate, we were also able to observe [3‐ 13 C]β‐OHB, in which the ratio of β‐OHB to acetoacetate can be used as a measure of redox state . The amplitude of [3‐ 13 C]β‐OHB, however, appeared to be an order smaller compared with the amplitude of [1‐ 13 C]β‐OHB in the study of Miller et al, which may be attributed to the lower T 1 of [3‐ 13 C]β‐OHB as well as the diabetic state of the GK rats compared with healthy rats. In the study of ketone body metabolism, hyperpolarized 13 C β‐OHB probe may be preferable as β‐OHB is the primary circulating ketone body.…”
Section: Discussionmentioning
confidence: 62%
“…Other hyperpolarized acetoacetate probes have also been reported (i.e. [1‐ 13 C]acetoacetate and [1,3‐ 13 C 2 ]acetoacetate) . Compared to [1‐ 13 C]acetoacetate, [3‐ 13 C]acetoacetate has the advantage of having the chemical shift downfield, away from the chemical shift of metabolic products, which allows more accurate quantification.…”
Section: Discussionmentioning
confidence: 99%
“…γ-glutamyl-[1-13 C]glycine fits the essential technical requirements of a useful HP probe 24 . Thanks to localization of the GGT enzyme on the outer surface of the cell membrane, γ-glutamyl-[1-13 C]glycine metabolism occurs in the extracellular space and not in the cytosol or mitochondria as is the case for most HP probes including HP [1-13 C]pyruvate 24 and [1-13 C]dehydroascorbic acid (DHA) 34,35 , or [1,3-13 C]acetoacetate [36][37][38] , respectively. This is a significant advantage as additional transport though the cell membrane would increase the time between HP injection and enzymatic reaction and therefore decrease SNR.…”
Section: Discussionmentioning
confidence: 99%